Functional Replacement of Nucleocapsid Flanking Regions by Heterologous Counterparts with Divergent Primary Sequences: Effects of Chimeric Nucleocapsid on the Retroviral Replication Cycle - Fu, William (American Society for Microbiology, 2003)
Nucleocapsid (NC) proteins in most retroviruses have a well-conserved Cys-His box(es) as well as more divergent flanking regions that are rich in basic residues. Mutations in the flanking regions can affect RNA packaging, virus assembly, and reverse transcription of the viral RNA. To gain a further understanding of the roles of NC flanking regions in the retroviral replication cycle, we generated and characterized chimeric gag-pol expression constructs derived from murine leukemia virus and spleen necrosis virus by replacing an NC flanking region from one virus with the counterpart from the other virus. We found that all four chimeras were able to generate virions, package viral RNA, and complete the viral replication cycle. Two chimeras had mild defects in virus assembly that correlated with a decrease in the isoelectric points of NCs, suggesting that the basic nature of NC is important in virus assembly. This finding indicates that, although the primary sequences of these flanking regions have little homology, the heterologous sequences are functional both as part of the Gag polyprotein and as processed NC protein.